Functional analyses of a novel leucine-rich repeat-containing protein, Elfn1, in the mouse - Dolan, Jackie N. (Trinity College (Dublin, Ireland). Department of Genetics, 2013)
The functional brain is critically dependent on a highly specific and perfectly timed gene-expression programme that underlies neuronal connectivity. Each step of this process, which includes cell migration, axon guidance, target selection and synaptogenesis, requires a vast number of molecules. While many genes with roles in these processes have been identified to date, the astonishing complexity and specificity of neural connections suggests that further molecules yetunidentified are involved. Leucine-rich repeat (LRR)-containing proteins are known to play crucial roles in the developing central nervous system. This led to the hypothesis that additional genes from this class of proteins could provide the necessary specificity of cellular interactions involved in neural connectivity.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.